1999
DOI: 10.1093/dnares/6.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Rice MADS Box Gene Homologues and Their RFLP Mapping

Abstract: Thirty-five MADS box gene homologues were identified through a large-scale cDNA analysis in rice. Based on the nucleotide sequences of the 3'-untranslated region, these clones were classified into 11 independent species. Seven species were found to be new among the rice MADS box gene family, and the other 4 corresponded to the previously reported OsMADS1, OsMADS2, OsMADS4, and OsMADS5. The full nucleotide sequences of the 7 new species were determined. Each clone encoded a deduced protein of 164-267 amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…In recent years, major progress has been made in understanding the evolutionary history of this gene family. From a phylogenetic point of view, the evolutionary history of the MADSbox gene family is characterized by frequent gene duplication and gene loss (Shinozuka et al 1999;Parenicova et al 2003;Hileman et al 2006; Leseberg et al 2006). Gene loss is regarded as the most likely fate for one of the duplicated copies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, major progress has been made in understanding the evolutionary history of this gene family. From a phylogenetic point of view, the evolutionary history of the MADSbox gene family is characterized by frequent gene duplication and gene loss (Shinozuka et al 1999;Parenicova et al 2003;Hileman et al 2006; Leseberg et al 2006). Gene loss is regarded as the most likely fate for one of the duplicated copies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kalanchoe pinnata transformed with the cDNA was also stimulated in branching (Kojima et al unpublished data). The results were, however, rather unexpected since it has been suggested that the cDNA is a member of AP1 MADS box genes based on the dendrogram analysis (Shinozuka et al, 1999). However, the nucleotide sequences of MADS box genes are highly conserved and very similar among various MADS box genes.…”
Section: The Plant Shapes Of T1 Plantsmentioning
confidence: 89%
“…Therefore, we tested this method using a rice cDNA (accession No. (DDBJ), AB003325) which had recently been cloned and defined (Shinozuka et al, 1999). The cDNA was expressed at a low level in panicles of rice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified the genes controlling flowering time in rice (Shinozuka et al, 1999;Izawa et al, 2003;Doi et al, 2004;Lee et al, 2005;Lu et al, 2006;Kim et al, 2007;Tamaki et al, 2007). The DNA sequences of these genes in strain 9311 of indica and strain Nipponbare of japonica were acquired by a rice genome search in the National Center for Biotechnology Information (NCBI) (http://www.ncbi.nlm.nih.gov/), the BGI-RIS (http://rise.genomics.org.cn/rice/index2.jsp), and the GRAMENE (http://www.gramene.org/ genome_browser/index.html) databases.…”
Section: Nipponbare (O Sativa Japonica)mentioning
confidence: 99%
“…Eighteen flowering time-controlling genes were selected according to published references (Shinozuka et al, 1999;Izawa et al, 2003;Doi et al, 2004;Lee et al, 2005;Lu et al, 2006;Kim et al, 2007;Tamaki et al, 2007). The sequences of these genes in Nipponbare (japonica) and 9311 (indica) were acquired by a search of rice genome in public databases (NCBI, BGI-RIS, and GRAMENE) and were aligned using Vector NTI advance 10 (data not shown).…”
Section: Screening For Genes Controlling Flowering Timementioning
confidence: 99%